Non-invasive interventions in idiopathic scoliosis: a systematic review - André Ivaniski Mello; Ana Carolina Kanitz; Flávia Gomes Martinez
Abstract Introduction: Idiopathic Scoliosis (IS) is an idiopathic curvature of the spine in all three plans, been treated conservatively (non-invasive) or surgicaly (invasive). The effectiveness of noninvasive therapy still remains lacking in a scientific basis to support their evidence-based applicability. Objective: Evaluate the effects of non-invasive interventions in spine lateral inclination in IS through a systematic literature review. Methods: The search of studies in MEDLINE, SCOPUS and COCHRANE databases was performed on 24th March, 2014. The terms used were: Scoliosis, therapeutic exercise, physical therapy. Clinical trials with scoliotic patients undergoing some type of non-invasive intervention were included. The outcome was spine lateral inclination. Results: The research found 941 studies, seven of these were included after a screening performed by two independent reviewers. Six studies (85.7%) have adopted some sort of kinesiotherapeutic technic, and three studies (42.8%) used corrective orthosis. The average intervention time in kinesiotherapeutic technique studies was of 37.6 weeks and 91.6 weeks in the studies of corrective brace. The progression improvement of the spine lateral inclination was reported by 83.3% (5 of 6) of the kinesiotherapeutic technique studies and in 66.6% (2 of 3) of studies with corrective brace. Conclusion: An improvement was found, in general, in the progression of spine lateral inclination in IS subjects of both sexes from 11 to 25 years of age undergoing non-invasive interventions.